Green ultrasound-assisted three-component click synthesis of novel 1H-1,2,3-triazole carrying benzothiazoles and fluorinated-1,2,4-triazole conjugates and their antimicrobial evaluation - Rezki Nadjet; Aouad Mohamed Reda (Acta Pharmaceutica)
The present study describes an efficient and ecofriendly, ultrasound, one-pot click cycloaddition approach for the construction of a novel series of 1,4-disubstituted-1,2,3-triazoles tethered with fluorinated 1,2,4-triazole-benzothiazole molecular conjugates. It involved three-component condensation of the appropriate bromoacetamide benzothiazole, sodium azide and 4-alkyl/aryl-5-(2-fluorophenyl)-3-(prop-2-ynylthio)-1,2,4-triazoles 4a-e through a Cu(I)-catalyzed 1,3-dipolar cycloaddition reaction. This approach involves in situ generation of azidoacetamide benzothiazole, followed by condensation with terminal alkynes in the presence of CuSO4/Na-ascorbate in aqueous DMSO under both conventional and ultrasound conditions. Some of the designed 1,2,3-triazole conjugates 6a-o were recognized for their antimicrobial activity against some bacterial and fungal pathogenic strains.